A risk-simulation based optimization model for wetland reallocation on Yongding floodplain, China. (April 2021) - Zeng, Xueting; Zhang, Shoujie; Li, Tienan; Xue, Yong; Zhao, Jinyong; Fu, Yicheng; Zhang, Jing; Chen, Cong; Kong, Xiangming; Zhang, Junlong
Graphical abstract: Highlights: Water is an indicator of wetland reallocation (WR) to recover the floodplain function. RTF method is proposed for reflecting risks and handling uncertainties in WR. Varied strategy scenarios (CFW and WD) are adopted to improve ecological values in WR. A rational WR plan can reduce risk and improve source function of floodplain. Tradeoff between land use and wetland protection can support to adjust current policy. Abstract: In this study, a wetland reallocation (WR) plan based on water-indicator is designed to confront various ecological crisis and flood risks on Yonding River Floodplain, China, where converting farmland to wetland (CFW) and water diversion (WD) can be considered to balance the tradeoff between manual land utilization and wetland conservation. A risk-simulation based two-stage stochastic fuzzy (RTF) method is developed for handling multiple uncertainties in a WR issue, which cannot only map various risks (including water shortage, soil loss, flood and pollution) through Geographic Information System (GIS), but also deal with objective / subjective uncertainties in a two-stage context. Through risk-simulation, numbers of risk maps have been obtained based on various WD scenarios, which displayed that ecological risk would be the lowest when water diversion reached 200 x 10 6 m 3, while flooding risk would increase. Meanwhile, based on WR optimization, natural-artificial wetland reallocations would decrease ecological loss about US$ 0.92 x 10 6 at highest. Moreover, the optimized land utilizations under various CFW and WD scenarios have been obtained. This study is useful for policymakers of floodplain to adjust current land utilization strategies with consideration of artificial regulations in a sustainable manner.